The Role of Marital Commitment and Family Support For Marital Satisfaction In Childless Couples - Anita Litawati Lioe (Eduvest - Journal of Universal Studies, 2023)
The course of married life, often colored by a variety of happy events or vice versa, contributes to marital satisfaction or dissatisfaction. The presence of children in married life will be one of the signs of achieving the goal of marriage. But in reality not all couples are blessed with children easily. Not having children in marriage can be one of life's disappointments that can affect marital satisfaction. In fact, what is more important than a marriage is not only the presence of children, but the success and satisfaction of marriage felt by the husband and wife. The satisfaction of married is largely determined by the internal and external factors of both partners. This study aims to determine the role of marital commitment and family support for marital satisfaction in childless couples. The study participants were 290 husbands and wives who had no children after more than five years of marriage. The data collection technique used snowball sampling, and was analyzed using multiple linear regression tests. The results of the study found that marital commitment and family support both play a role in marital satisfaction in couples who have been married for more than five years. Simultaneously, the length of marriage also predicts marital satisfaction.